Design a Complete Website for the Sustainable Development Goals (SDG) in Iraq - Amer S. Elameer; Methaq Khamis; Amjed Abbas (QALAAI ZANIST JOURNAL, 2021)
17 goals and 169 targets have been announced by the United Nations at the summit held in September 2015 to achieve comprehensive development in all social, economic and environmental aspects to improve life. However, the achievement of these goals requires a change in mentality and culture of design development strategies where information plays a key role in its success if it has been delivered to communities effectively. Websites have active role in providing information for different people free of charge. The research aims to improve the current developed condition of Iraq through publishing the cultural awareness of sustainable development and its goals among people via the new technology tools, as well as helping professionals in the field of sustainable development in identifying problems and finding proper solutions. The problem of research is educating the community to actively participate in achieving the goals of sustainable development, especially after the significant decline experienced by Iraq in achieving the MDG after 2014. The first website is designed for the purpose of SDGs. This website is designed to publish the SDGs and their targets as well as the statistics that relate to them. Different programming languages have been used in designing this website such as PHP, HTML, CSS, JavaScript, Jquery, AJAX and MySQL.